Myomectomy: TU Teaching Hospital experiences - Gurung, Geeta; Pradhan, Neelam; Rawal, Suniti; Rana, Ashma; Ghimire, seeta; Baral, Josie (Nepal Journal of Obstetrics and Gynaecology, 2010)
Aim: To study, open myomectomy operation for uterine myoma/s as of present day practices in women of reproductive age attending TU Teaching Hospital. Methods: This is a retrospective study where we reviewed the medical records of myomectomy cases from 2060-2065(2003 April-2009 April). Result: Total 40 cases of myomectomy performed in TU Teaching hospital for myoma size varying from ≥ 10 weeks (5), 12-16 weeks (15), 17-22 weeks (5), 23-28 weeks (5) and unknown (2) in women of reproductive age [ 30-34(16), ≥ 29 (13), 35-39 (9), 40- 44 (1) and ≥ 45 (1)] in 13 (unmarried); nullipara (17); P1-2 (15) P3-4 (1) for reasons of infertility(12), dysmenorrhea (12), menorrhagia (8), urinary problems( 7) abdominal pain (3). At caesarean, myomectomy has been done in special circumstances for subbersous pedunculated myoma and broad ligament myoma, one each. Solitary myomas were 29 and multiple myomas were 8; a case each of broad ligament and cervical myoma (1), was later removed vaginally. Rests had abdominal procedure and was facilitated by Bonney's hood incision and posterior incision 8 each, anterior 7, fundal 2, using multiple incision technique in 11 along with secondary tunneling incision (3). Uterine cavity was opened in 3 resulting in blood loss up to ≥ 500ml in 2. Degeneration were noticed in 11 [cystic (4), fatty (2), calcification (2) red (2) and myxoid (1)] and none with post operative morbidity. Pregnancies were recorded in 3 cases. Conclusion: Open abdominal myomectomy, for uterine myoma/s has been a recognized procedure for infertile women in the past; but in view of less morbidity as shown by this present study myomectomy can be safely practiced in women desiring uterine preservation besides infertility care. . Key words: Degeneration; dysmenorrhoea; menorrhagia; myomectomy DOI: 10.3126/njog.v4i1.3326 Nepal Journal of Obstetrics and Gynaecology June-July 2009; 4(1): 15-18